It’s about me! My approach to autoethnography - Rangiwai, Byron (Te Kaharoa, 2021)
Autoethnography is about me as the writer and researcher exploring my lived experiences (Ballard, 2009; Ritchie et al., 2013) as a form of storytelling (Jones, 2003). It is a genre of writing that “shows struggle, passion, [and] embodied life” (Ellis & Bochner, 2006, p. 433) and provides “highly personalised accounts that draw upon the experience of the author/researcher”.